Cancer immunotherapy in special challenging populations: recommendations of the Advisory Committee of Spanish Melanoma Group (GEM). Issue 3 (29th March 2021) - Gonzalez-Cao, Maria; Puertolas, Teresa; Riveiro, Mar; Muñoz-Couselo, Eva; Ortiz, Carolina; Paredes, Roger; Podzamczer, Daniel; Manzano, Jose Luis; Molto, Jose; Revollo, Boris; Carrera, Cristina; Mateu, Lourdes; et al.
Abstract : Cancer immunotherapy based on the use of antibodies targeting the so-called checkpoint inhibitors, such as programmed cell death-1 receptor, its ligand, or CTLA-4, has shown durable clinical benefit and survival improvement in melanoma and other tumors. However, there are some special situations that could be a challenge for clinical management. Persons with chronic infections, such as HIV-1 or viral hepatitis, latent tuberculosis, or a history of solid organ transplantation, could be candidates for cancer immunotherapy, but their management requires a multidisciplinary approach. The Spanish Melanoma Group (GEM) panel in collaboration with experts in virology and immunology from different centers in Spain reviewed the literature and developed evidence-based guidelines for cancer immunotherapy management in patients with chronic infections and immunosuppression. These are the first clinical guidelines for cancer immunotherapy treatment in special challenging populations. Cancer immunotherapy in chronically infected or immunosuppressed patients is feasible but needs a multidisciplinary approach in order to decrease the risk of complications related to the coexistent comorbidities.